Pastors as gewonde genesers: Outobiografiese pastoraat as heelmiddel vir emosionele verwonding en verlamming by pastors - Nolte, S. Phillip (HTS teologiese studies, 2009)
Pastors as wounded healers: Autobiographical pastorate as a way for pastors to achieve emotional wholenessIn a previous article it was argued that pastors suffer from cognitive dissonance because of the paradigm shift from modernity to postmodernity, and the emotional woundedness that frequently results from their struggles to come to terms with the new world in which they have to live and minister. This article reflects on the way in which two further issues may exacerbate emotional woundedness in pastors. The one is church tradition, as it is reflected in several formularies used during church services in the Nederduitsch Hervormde Kerk van Afrika (NHKA), as well as the Church Ordinance of the NHKA. The other issue is the way in which pastors view the Bible. The language and rhetoric used to reflect on these issues are discussed and evaluated. In its last paragraph the article reflects on the possibility of autobiographical pastorate as a way for pastors to achieve emotional wholeness.